To solve the expression \(-24 \frac{4}{5} - 6 \frac{7}{10}\) using the additive inverse, we first convert the mixed numbers to improper fractions.
-
Convert \(-24 \frac{4}{5}\) to an improper fraction: \[ -24 \frac{4}{5} = -\left(24 \times 5 + 4\right) = -\left(120 + 4\right) = -124 \text{ (as an improper fraction)} = -\frac{124}{5} \]
-
Convert \(-6 \frac{7}{10}\) to an improper fraction: \[ -6 \frac{7}{10} = -\left(6 \times 10 + 7\right) = -\left(60 + 7\right) = -67 \text{ (as an improper fraction)} = -\frac{67}{10} \]
Next, unite the two fractions \(-\frac{124}{5}\) and \(-\frac{67}{10}\). To add these fractions, we need a common denominator. The least common multiple of 5 and 10 is 10.
- Convert \(-\frac{124}{5}\) to a denominator of 10: \[ -\frac{124}{5} = -\frac{124 \times 2}{5 \times 2} = -\frac{248}{10} \]
Now we can add the two fractions: \[ -\frac{248}{10} - \frac{67}{10} = -\frac{248 + 67}{10} = -\frac{315}{10} \]
- Simplify \(-\frac{315}{10}\): \[ -\frac{315}{10} = -31 \frac{5}{10} = -31 \frac{1}{2} \]
So, the final answer is: \[ \boxed{-31 \frac{1}{2}} \]